Network Folklore and its Role in the Formation of a Collective Cognitive Space - Belovodskaja, Anastasija (Respectus Philologicus, 2014)
The global implementation of information-communicative technologies into every sphere of human activity is being accompanied by the emergence of new forms of communication, leading to inevitable changes in the means of both the representation and reception of information. In this respect, the field of interest encompasses research into modern anonymous network creative writing, which, as a result of the technological qualities of the Internet space, produces such texts that require particular skills in both comprehension and reproduction. In turn, the products of network folklore, as they spontaneously spread on the Internet, acquire the status of particular signs of a precedent nature. At the same time, the very nature of anonymous network creative writing—amusing and colloquial—raises the attractiveness of such texts and facilitates their reception, allowing them to be used for manipulative aims. The fact that such network folklore can influence the process of idea-formation in society is predetermined by the fact that, by definition, it is the milieu where collective representations are condensed and transmitted. Thus, network folklore is in the focus of attention not only in folklore studies, but is extremely topical for research in such fields as cognitive science, linguistic-cultural studies, public relations, speech effect, and any others which take interest in the processes of keeping, receiving, and transmitting information.